Resolving consecutive excited-state evolution in Fe-amido chromophores by wide-band optical transient absorption spectroscopy - Wegeberg, Christina; Sidhu, Baldeep K.; Chábera, Pavel; Uhlig, Jens ; 0000-0002-0528-0422; Cowin, Rory A.; Weinstein, Julia A.; Persson, Petter; Yartsev, Arkady ; 0000-0003-4941-4848; Herbert, David E. (Chemical Science, 2026)
A detailed understanding of excited-state evolution is critical to realizing the full potential of abundant-metal coordination complex photosensitizers. Here, we show how wide-band optical transient absorption spectroscopy (oTA) can delineate the complete energy relaxation pathway of the photoexcited state of Fe(ii) polypyridyl complexes supported by benzannulated diarylamido ligands. By covering a broader spectral region from 370 to 1200 nm, we resolve consecutive evolution of a photoexcited Fe-amido chromophore from an initially generated singlet ‘π-antibonding-to-ligand’ charge transfer (1PALCT) excited state to a long-lived metal-centred quintet (5MC) via both a 3PALCT and what we assign as a 3MC state. Notably, we identify spin-parity transformations by observing photogeneration of the 1PALCT followed by its conversion into a 3PALCT state, and the subsequent 3MC-to-5MC transformation via observation of an isosbestic point in the oTA spectral dynamics. The state-to-state transformations are accompanied by coherent oscillations which are impulsive Raman-induced, originating in the ground state. Combining high-resolution, wide-band oTA experiments with the unique absorptive properties of diarylamido ligand–metal complexes, we are thus able, for the first time, to trace the complete deactivation trajectory of an iron(ii) polypyridyl sensitizer using optical spectroscopy.
Publisher Copyright: This journal is © The Royal Society of Chemistry, 2026